2002
DOI: 10.1007/s00420-001-0302-4
|View full text |Cite
|
Sign up to set email alerts
|

Occupational respiratory hypersensitivity in dental personnel

Abstract: Objective: The aim was to study the causes of respiratory hypersensitivity in dental personnel based on the statistics of the Finnish Register of Occupational Diseases (FROD; 1975-1998 and the patient material of the Finnish Institute of Occupational Health (FIOH; 1990-1998. Methods: Details about the cases of respiratory hypersensitivity were compiled from the FROD. The occupational rhinitis diagnoses studied at the FIOH were based on work-related symptoms and a change in the status of the nasal mucosa durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 27 publications
0
58
0
3
Order By: Relevance
“…Although the field researcher was not able to verify that these systems delivered fresh air or that these systems were appropriately designed and operated, he did verify that these systems were functional. As shown in Table 4, the salons in the sample rely on a variety of strategies to move and condition air, including room air conditioning units (20), room and table fans (16), open doors and windows (13), stand-alone air cleaners units (5), and wall or ceiling mounted exhaust fans (5). One salon had built a "local exhaust" system whereby commercial vacuum cleaners in the basement were connected to a work area by a hose extended through the ceiling to the tables above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the field researcher was not able to verify that these systems delivered fresh air or that these systems were appropriately designed and operated, he did verify that these systems were functional. As shown in Table 4, the salons in the sample rely on a variety of strategies to move and condition air, including room air conditioning units (20), room and table fans (16), open doors and windows (13), stand-alone air cleaners units (5), and wall or ceiling mounted exhaust fans (5). One salon had built a "local exhaust" system whereby commercial vacuum cleaners in the basement were connected to a work area by a hose extended through the ceiling to the tables above.…”
Section: Resultsmentioning
confidence: 99%
“…John et al found that manicurists and nail sculptors were at increased risk of spontaneous abortion [10]. Health effects have been well documented in other workers, such as dental technicians, who work with one of the principal chemicals used in nail salons: ethyl methacrylate [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory hypersensitivity represents another occupational health issue for dentists, with a Finnish investigation suggesting that its prevalence among dental personnel may be increasing 78) . The causes of respiratory hypersensitivity amongst dentists include MMA, latex, and c h l o r a m i n e -T ( s o d i u m -N -c h l o r i n e -p -t o l u e n e sulphonamide) 78) .…”
Section: Dermatitis and Respiratory Hypersensitivitymentioning
confidence: 99%
“…The causes of respiratory hypersensitivity amongst dentists include MMA, latex, and c h l o r a m i n e -T ( s o d i u m -N -c h l o r i n e -p -t o l u e n e sulphonamide) 78) . Trace toxic metals such as beryllium, may also be generated from dental materials which contain alloys of beryllium 61) .…”
Section: Dermatitis and Respiratory Hypersensitivitymentioning
confidence: 99%
“…The Finnish Register of Occupational Diseases diagnosed 24 cases of occupational asthma or rhinitis caused by methacrylates during the years 1990-98 .The incidence rate of occupational respiratory disease was considered greater than in the whole population (Piirilä et al 2002) Preventive actions such as change in hygiene factors, use of no-touch techniques when working with methacrylates, less use of latex and awareness of risk factors seems to keep the prevalence of skin and respiratory symptoms low among dental personnel (Schedle et al 2007).…”
Section: Epidemiological and Clinical Evidence Concerning Adverse Effmentioning
confidence: 99%